The antecedents of supply chain agility of a firm: Scale development and model testing - Swafford, Patricia M.; Ghosh, Soumen; Murthy, Nagesh (Journal of Operations Management, 2006)
AbstractIn a constantly changing global competitive environment, an organization's supply chain agility directly impacts its ability to produce, and deliver innovative products to their customers in a timely and cost effective manner. While the beneficial impact of supply chain agility is generally acknowledged, very little research exists to date addressing how an organization can achieve supply chain agility. This study first presents a framework of an organization's supply chain process flexibilities as an important antecedent of its supply chain agility, and then establishes the key factors that determine the flexibility attributes of the three critical processes of the supply chain—procurement/sourcing, manufacturing, and distribution/logistics. Using empirical data, we develop flexibility and agility scales related to our supply chain agility model, and then test the model. Findings reveal that supply chain agility of a firm is directly and positively impacted by the degree of flexibility present in the manufacturing and procurement/sourcing processes of the supply chain; while it is indirectly impacted by the level of flexibility within its distribution/logistics process. The results also support our view that a firm's supply chain agility is impacted by the synergy among the three process flexibilities in its internal supply chain.